Impact of Zinc Oxide Nanoparticles on Growth and Plant Growth-Promoting Traits of Bacillus subtilis, Azospirillum lipoferum and Bacillus licheniformis - Swapnil Srivastava; Manoj Kumar Yadav; Vaishali; Lokesh Kumar Gangwar; Ramji Singh; Ravinder Kumar; Uday Pratap Shahi (The Bioscan, 2026)
The integration of zinc oxide nanoparticles (ZnO-NPs) with plant growth-promoting rhizobacteria (PGPR) represents a promising strategy for sustainable agriculture, yet the compatibility between these nano-inputs and beneficial microorganisms remains poorly understood.